The relationship between inflation and interest rates in the UK: The nonlinear ARDL approach - Ismet Gocer; Serdar Ongan (Journal of Central Banking Theory and Practice, 2020)
This study reconsiders the Fisher effect for the UK from a different methodological perspective. To this aim, the nonlinear ARDL model recently developed by Shin et al. (2014), is applied over the periods of 1995M1-2008M9 and 2008M10-2018M1. This model decomposes the changes in original inflation series as two new series: increases and decreases in inflation rates. Hence, it enables us to examine the Fisher effect in terms of increases and decreases in inflation separately. The empirical findings support asymmetrically partial Fisher effects for the UK in the long-run only for the first period. Additionally, this study attempts to describe and introduce a different version of the partial effect concept for the first time for the UK.
Keywords: E40; E43; G12; 330; Fisher effect; Nonlinear ARDL; the UK's treasury bond rates